2007
DOI: 10.1084/jem.20061929
|View full text |Cite
|
Sign up to set email alerts
|

Increased susceptibility to colitis and colorectal tumors in mice lacking core 3–derived O-glycans

Abstract: Altered intestinal O-glycan expression has been observed in patients with ulcerative colitis and colorectal cancer, but the role of this alteration in the etiology of these diseases is unknown. O-glycans in mucin core proteins are the predominant components of the intestinal mucus, which comprises part of the intestinal mucosal barrier. Core 3–derived O-glycans, which are one of the major types of O-glycans, are primarily expressed in the colon. To investigate the biological function of core 3–derived O-glycan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
278
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 298 publications
(287 citation statements)
references
References 64 publications
6
278
0
3
Order By: Relevance
“…It is known that mature O‐glycosylation depends specifically on T‐synthase activity and its single chaperone‐Cosmc 31. Besides, in colonic tissues, defective core 3 O‐glycosylation could also lead to the exposure of Tn antigen 21, 32. Here we found that the expression of C3GnT that controls core 3 O‐glycosylation in cancer tissues expressing Tn antigen (Tn‐positive) was comparable to that in Tn‐negative cancerous tissues, thereby suggesting that there were only possible defects in T‐synthase and/or Cosmc (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…It is known that mature O‐glycosylation depends specifically on T‐synthase activity and its single chaperone‐Cosmc 31. Besides, in colonic tissues, defective core 3 O‐glycosylation could also lead to the exposure of Tn antigen 21, 32. Here we found that the expression of C3GnT that controls core 3 O‐glycosylation in cancer tissues expressing Tn antigen (Tn‐positive) was comparable to that in Tn‐negative cancerous tissues, thereby suggesting that there were only possible defects in T‐synthase and/or Cosmc (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, these studies also identified O-glycans on mammalian Tango1/Mia3 (26,27), suggesting that O-glycans may perform similar protective functions to control secretion in mammalian systems. Indeed, alterations in both Tango1/Mia3 and O-glycosylation have been associated with diseases of the mammalian gastrointestinal tract (5,6,28,29), which are typically characterized by loss of secretion, loss of mucous membrane formation, and increased diffusion barrier permeability. Interestingly, PGANT4 is most similar to the mammalian ppGalNAc-T10 (8), which is abundantly expressed in the digestive system (30).…”
Section: Resultsmentioning
confidence: 99%
“…Polarized secretion is also required in many differentiated tissues, such as the digestive tract, where secreted components along the apical surface form the mucous membrane that confers protection from mechanical and microbial insults (1) and provides immunoregulatory signals (2). Indeed, disruptions in the secreted mucous membrane are associated with diseases of the digestive tract, such as colitis and colon cancer (3)(4)(5)(6).…”
mentioning
confidence: 99%
“…Mucin dysfunction 33, 34 and JAM‐A deficiency 35, 36 have been shown to cause increased intestinal permeability, especially under basal conditions, with an enhanced susceptibility to experimental colitis. Thus, we evaluated mucin production in CerS2 null mice.…”
Section: Resultsmentioning
confidence: 99%
“…These two layers are organized into a net‐like polymer around mucin 2, the most abundant mucin protein, which is heavily glycosylated and secreted by goblet cells 33. Mucin can be detected by PAS and alcian blue staining (PAS detects neutral carbohydrates, whereas alcian blue recognizes acidic carbohydrates that represent sialylated, fucosylated or sulphated sugars 34). However, PAS and alcian blue staining were normal in the colon of CerS2 null mice (Fig.…”
Section: Resultsmentioning
confidence: 99%